Five Decades of Achievement Motivation Research In ELT: A Systematic Literature Review - Shurovi, Marzia; Yahaya, Mohamad Fadhili; Hajimia, Hafizah; Hasan, Md Kamrul (Universiti Utara Malaysia Press, 2024)
Purpose – There is an absence of systematic review papers in the achievement motivation theories literature. In terms of current research trends, English learning motivation is gaining attention as a determiner of success in FLA. Hence, this review aims to trace the trends in the empirical studies on achievement motivation theories and tools, ranging from 1970 to 2022.